2004
DOI: 10.1124/jpet.104.071266
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nonpeptide Antagonist of the Kinin B1Receptor: Effects at the Rabbit Receptor

Abstract: The kinin B 1 receptor (B 1 R) has attracted interest as a potential therapeutic target because this inducible G protein-coupled receptor is involved in sustained inflammation and inflammatory pain production.is a high-affinity nonpeptide antagonist for the human B 1 R, but it is potent at the rabbit B 1 R as well: its K i value for the inhibition of [ The kinin B 1 receptor (B 1 R) is a G protein-coupled receptor selectively stimulated by sequences related to bradykinin (BK) but not by BK itself. Instead, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…This effect was also seen with IL-1␤ and PMA, with a nonsignificant concentration decrease with actinomycin D treatment. The B 1 receptor agonist Lys-des-Arg 9 -BK had no significant effect on B 1 receptor mRNA concentration (with or without actinomycin D); compound 11 (100 nM, data not shown), a high affinity nonpeptide antagonist of the B 1 receptor (Morissette et al, 2004), had no effect as well.…”
Section: Effects Of Stimulants Onmentioning
confidence: 92%
“…This effect was also seen with IL-1␤ and PMA, with a nonsignificant concentration decrease with actinomycin D treatment. The B 1 receptor agonist Lys-des-Arg 9 -BK had no significant effect on B 1 receptor mRNA concentration (with or without actinomycin D); compound 11 (100 nM, data not shown), a high affinity nonpeptide antagonist of the B 1 receptor (Morissette et al, 2004), had no effect as well.…”
Section: Effects Of Stimulants Onmentioning
confidence: 92%
“…However, Sabourin et al (2002) have observed a special form of agonist-induced translocation using a fusion protein composed of the rabbit B 1 receptor conjugated to the yellow fluorescent protein (B 1 R-YFP): the smooth membrane distribution of the receptor-associated fluorescence evolved toward condensed structures that remained associated with the plasma membrane. This translocation was inhibited by pharmacological antagonists of the B 1 receptors, showing that this response is dependent on a form of signaling, and also by cell pretreatment with ␤-cyclodextrin, supporting that the structures where B 1 R-YFP concentrate are a variety of cholesterol-rich rafts (Sabourin et al, 2002;Morissette et al, 2004). Furthermore, unlike the stable B 2 receptors, the B 1 receptors are apparently short-lived at the cell surface, where they are cleared in a ligand-independent manner (Fortin et al, 2003).…”
mentioning
confidence: 88%
“…Staining by fluorescent antagonists was not conferred by the empty FLAG vector and was greatly reduced by cotreating receptorexpressing cells with the high-affinity nonpeptide antagonist, compound 11 (Fig. 4) (Morissette et al, 2004). The B 1 receptor agonist B-10378 also labeled cells that expressed recombinant B 1 R-FLAG or rabbit B 1 receptors (50 nM, 30-min treatment, Fig.…”
Section: Radioligand Binding Competition Assay the Displacement Of [mentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Tissue treatment with the powerful and specific nonpeptide B 1 receptor antagonist, compound 11 (1 nM) [18], shifted the concentration-effect of Lys-des-Arg 9 -BK to the right and abolished the effect of the submaximal concentration of Met-Lys-BK-Ser-Ser, supporting that both agents contracted the tissue via B 1 receptors. The contractile effects of Met-Lys-BK-Ser-Ser or of Lys-des-Arg 9 -BK were not modified by co-incubation with the ACE inhibitor enalaprilat (100 nM inhibitor (1 µM), a blocker of arginine carboxypeptidases that removes the C-terminal arginine from native kinins ( Fig.…”
Section: Contractility Assaysmentioning
confidence: 85%